The forgotten front : the Eastern Theater of World War I, 1914-1915 - Gross, Gerhard Paul, 1958-; Ancker, Janice W. (Foreign military studies (Lexington, Ky.), 2018)
This text presents research on the eastern front of World War I, a subject comparatively eclipsed by scholarly study of the western front. Focusing on the first two years of the war, the volume concentrates primarily on elements of the conflict between the Central Powers (specifically Germany and its ally Austria-Hungary) and pre-revolutionary Russia. The work approaches topics of interest through a tripartite structure, addressing the operational conduct of the war, the combatants' cultural conceptions of themselves and the enemy, and how the conflict has been understood and commemorated in the years since the end of the war. The volume concludes with a chapter that brings together themes studied throughout the text in a discussion of the potential continuities between the German conduct and perception of war from the First World War to the Second.